Botryoid odontogenic cyst developing from lateral periodontal cyst: A rare case and review on pathogenesis - Piyush Arora; Kundendu A Bishen; Nishant Gupta; Anshuman Jamdade; Gopa R Kumar (Wolters Kluwer Medknow Publications, 2012)
Botryoid odontogenic cyst (BOC) is considered to be a polycystic variant of the lateral periodontal cyst (LPC) as the specimen resembled a cluster of grapes. It is a non-inflammatory odontogenic cyst. The BOCs can be unicystic or multicystic. These cysts have potential to extend in the bone and become multilocular and they have a high recurrence rate. Till now, only 73 cases of BOC have been reported. The pathogenesis of BOC is still debatable. We review different pathogenesis proposed for BOC and discuss a rare case of BOC developing from lining of an abnormally large LPC which showed aggressive behaviour in terms of growth and size.